DIGITAL TRANSFORMATION IN THE CREATIVE ECONOMY: OPPORTUNITIES AND RISKS - Senduk, Feibry Feronika Wiwenly; Pongayouw, Syalomitha; Mokoginta, Riza (EDUCATIONE, 2025)
This research aims to analyze the impact of digital transformation on strengthening the creative economy sector, focusing on three main subsectors in Tomohon City, namely culinary, handicrafts, and fashion. The research approach used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observations, and documentation. The results of the study show that digitalization has brought significant changes to the way MSMEs produce, transact, and market products. In the culinary subsector, digital technology is mainly used for payment systems and delivery services. In the handicraft subsector, social media is the main means of promoting and strengthening product image. Meanwhile, the fashion subsector showed the highest digital integration through the use of various online platforms and data-based financial management systems. Digital transformation has proven to be able to increase efficiency, expand markets, and strengthen local brand identities, but it also presents challenges in the form of low digital literacy, limited infrastructure, and data security risks. This research emphasizes the importance of strategies for increasing the digital capacity of MSME actors as well as supporting policies that favor equitable access to technology. Thus, digital transformation is not only a tool for adaptation, but also a key driver in building an inclusive and sustainable creative economy ecosystem in the digital era.